O sprzedaży wiedzy w firmie szkoleniowej i dyfuzji standardów - Woźniak, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Descriptions of the mechanisms of the knowledge management need to consider the specifics of the various segments of the professional services. An example from a soft skills training company is used to describe the company's knowledge system and how it differs from the knowledge system of a consulting company described in [16]. Examples of training programmes are shown, to illustrate two types of knowledge-based income generation. In the first, knowledge data-bases are used to lower the cost of operational activity. In the second, a new product for the client is created, through giving him access to the training company's knowledge database. The dilemma of how to sell training modules, which the client's internal trainers are to conduct for the client's employees, and how to protect this knowledge from spreading to other companies, is described. The solution to this dilemma may be the reason why there is a pressure to create fashions in the consultancy market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 629-645